Development of a methodological framework and supporting data base for air pollution impact scoping in South African industrial planning - Scorgie, Yvonne (My University, 2014)
The principles of Integrated Environmental Management have been adopted by South Africa, and mandatory environmental scoping and impact assessments recently introduced. Air pollution scoping studies have, however, been hindered by the absence of objective scoping criteria and a readily accessible atmospheric dispersion climatology data base. The purpose of this research was to develop a conceptual methodological framework within which industrial planners may assess whether proposed developments will impact significantly on the air quality of the receiving environment. The primary function of the conceptual framework is the identification of pertinent data, and the integration of such data into the decision making process. The study comprises the development of several data and model bases including: an industrial data and model base to facilitate the inventory of emissions from proposed iron and steel industries; an ambient air quality data and model base able to characterise the existing air quality at the proposed site; an atmospheric dispersion, climatology data and model base to parameterise and reconcile the macro- and meso-scale ventilation potentials of the site; and an environmental risk identification data and model base to assess the sensitivity of the receiving environment. The methodological framework includes a procedure for the integration of the findings of the industrial, ambient air quality, atmospheric dispersion potential and risk identification model bases into the final decision making process. The decision-making framework proposed is designed to ensure that informed, transparent and reproducible decisions are made with regard to the acceptability of the proposed development, or the need for further assessment. Such a framework could enhance communication, promote the review of project options early on in the planning phase, and assist in the resolution of disputes regarding the proposed process. In instances where no compromises are possible, or where the impact of the proposed development requires fuiiiici study, the methodological framework can provide useful baseline information and establish the precedent for transparency and consistency in the subsequent air pollution impact assessments. The practical applicability of the methodological framework has been evaluated, based on a review of the various assumptions made and of the potential model-output inaccuracies related to the unavailability of data. The utility of the framework could most effectively be enhanced through the expansion of the industrial data base to include further types of industries, and the extension of the dispersion climatology data and model base to allow for the parameterisation of meso-ventilation potentials at coastal sites.